Respuesta :

Answer:7n-1

Step-by-step explanation:

Nth term=6+7(n-1)

Nth=6-7+7n

Nth term=-1+7n

Nth term=7n-1

The nth term rule of the linear sequence is 7n - 1.

This is an arithmetic progression and the formula used for the calculation will be:

Tn = a + (n - 1)d

where,

a = first term = 6.

n = number of terms

d = common difference = 13 - 6 = 7

Therefore, we'll slot the values into the equation. This will be:

Tn = a + (n - 1)d

= 6 + (n - 1)7

= 6 + 7n - 7

= 7n - 1

Therefore, the nth term will be 7n - 1.

Read related link on:

https://brainly.com/question/7565736